Hospitalizations for Diarrhea in Quebec Children from 1985 to 1998: Estimates of Rotavirus-Associated Diarrhea - René-Pierre Buigues; Bernard Duval; Louis Rochette; Nicole Boulianne; Monique Douville-Fradet; Pierre Déry; Gaston De Serres (Canadian Journal of Infectious Diseases)
OBJECTIVE: To characterize the incidence and duration of hospitalization due to diarrhea and to assess the proportion of hospitalizations that are attributed to rotavirus-associated diarrhea.